2004
DOI: 10.1152/ajpregu.00103.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mice with deletion of the mitochondrial glycerol-3-phosphate dehydrogenase gene exhibit a thrifty phenotype: effect of gender

Abstract: To define the role of mitochondrial glycerol-3-phosphate dehydrogenase (mGPD; EC 1.1.99.5) in energy balance and intermediary metabolism, we studied transgenic mice not expressing mGPD (mGPDϪ/Ϫ). These mice had Ϸ14% lower blood glucose; Ϸ50% higher serum glycerol; Ϸ80% higher serum triglycerides; and at thermoneutrality, their energy expenditure (QO2) was 15% lower than in wild-type (WT) mice. Glycerol-3-phosphate levels and lactate-to-pyruvate ratios were threefold elevated in muscle, but not in liver, of mGP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…It therefore appears that Pten deletion may produce some different physiological effects dependent on gender. Although the underlying mechanism for this phenomenon is not clear at this point, our data are consistent with multiple knockout experiments targeting signaling pathways involved in the regulation of energy homeostasis that yielded as-yet unexplained gender-specific phenotypes (41)(42)(43). Thus, this is an area that clearly deserves further detailed analysis.…”
Section: Discussionsupporting
confidence: 83%
“…It therefore appears that Pten deletion may produce some different physiological effects dependent on gender. Although the underlying mechanism for this phenomenon is not clear at this point, our data are consistent with multiple knockout experiments targeting signaling pathways involved in the regulation of energy homeostasis that yielded as-yet unexplained gender-specific phenotypes (41)(42)(43). Thus, this is an area that clearly deserves further detailed analysis.…”
Section: Discussionsupporting
confidence: 83%
“…In rodents, mGPD is highly expressed in BAT (Ohkawa et al, 1969). In the mouse, skeletal muscle ranks second, next to BAT in mGPD abundance, followed by brain, kidney and liver (Koza et al, 1996), which we have just confirmed (Alfadda et al, 2004). This hierarchy is similar in the rat (Lee and Lardy, 1965).…”
Section: Nadh Shuttle and Th Thermogenesissupporting
confidence: 72%
“…Results have been recently published (Alfadda et al, 2004;DosSantos et al, 2003). The most salient characteristics of the phenotype are summarized in Table 1.…”
Section: Nadh Shuttle and Th Thermogenesismentioning
confidence: 99%
See 2 more Smart Citations